Perencanaan Bisnis Desain Website - Irvan Sunardi (Universitas Tarumanagara, 2021)
Website design is the process of planning, conceptualizing, and managing content intended for the Internet. Modern website design goes beyond how things look (aesthetically) to include the way things work (functionality). Website design is not limited to website sites because it includes other uses such as web applications, mobile applications, and user interface designs.